Clinical and molecular spectrum and prognostic outcomes of U2AF1 mutant clonal hematopoiesis- a prospective mayo clinic cohort study. (February 2023) - Pritzl, Stephanie L.; Gurney, Mark; Badar, Talha; Ferrer, Alejandro; Lasho, Terra; Finke, Christy; Mangaonkar, Abhishek; McCullough, Kristen; Gangat, Naseema; Fernandez, Jenna; Al-Kali, Aref; Viswanatha, David; et al.
Highlights: U2AF1 CH is infrequent in age-related CH (<10 %) and commonly presents as CCUS. . U2AF1 CH is common in males and frequently co-occurs with BCOR mutations (29 %; 86 % occurring in males). U2AF1 mutant CH is associated with a high rate (25 %) and short latency (17.5 months) for progression to myeloid neoplasms. U2AF1 CH occurs in the elderly and the context-specific occurrence in younger patients with TBD needs assessment.